Volume 3: 19th International Conference on Design Theory and Methodology; 1st International Conference on Micro- And Nanosystem 2007
DOI: 10.1115/detc2007-34600
|View full text |Cite
|
Sign up to set email alerts
|

A Polynomial-Chaos-Based Bayesian Approach for Estimating Uncertain Parameters of Mechanical Systems

Abstract: Advanced Vehicle Dynamics LabCenter for Vehicle Systems and Safety, Virginia Tech, Blacksburg, VA 24061-0238 ABSTRACT This is the first part of a two-part article. A new computational approach for parameter estimation is proposed based on the application of the polynomial chaos theory. The polynomial chaos method has been shown to be considerably more efficient than Monte Carlo in the simulation of systems with a small number of uncertain parameters. In the new approach presented in this paper, the maximum lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…First, the holding constraint is active and then the system transitions to the flat 12 constraints may be defined as, (45) represent scaling factors of the conditions from a standard deviation perspective. The uncertain holding constraint (46) result in a reduced set of efficient operations on the eviation sense. This means a subset of the systems still not satisfy the constraints.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the holding constraint is active and then the system transitions to the flat 12 constraints may be defined as, (45) represent scaling factors of the conditions from a standard deviation perspective. The uncertain holding constraint (46) result in a reduced set of efficient operations on the eviation sense. This means a subset of the systems still not satisfy the constraints.…”
Section: Resultsmentioning
confidence: 99%
“…Sandu and coworkers introduced its application to multibody dynamical systems in [27,28,[36][37][38][39][40]. Significant work has been done applying it as a foundational element in parameter [23][24][25][26][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] and state estimation [60,61], as well as system identification [62]. Relatively recent work has applied gPC to both classical and optimal control system design [41,63,64].…”
Section: 25mentioning
confidence: 99%
“…Blanchard et al [1] showed that the maximum likelihood estimate is given by that realization of the parameters (that value of ξ) which maximizes the a posteriori probability P[θ|z], or, equivalently, minimizes −log(P[θ|z]), where z is the latest, yet-to-beused set of observations. This value of ξ corresponding to the maximum likelihood estimate is given by…”
Section: Polynomial-chaos-based Bayesian Approachmentioning
confidence: 99%
“…where F K 1 , F K 2 , F C 1 , and F C 2 are defined in equations (32) and (33). In these equations, the variables are expressed versus their position at equilibrium (if the added mass M is not in the middle, static deflections occur).…”
Section: Roll Plane Modelling Of a Vehiclementioning
confidence: 99%
See 1 more Smart Citation